A Scoping Review of the Health Technology Procurement Decision Process in Indonesia - Cashin, Andrew; Tumanggor, Roxsana Devi (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: There is no doubt technological development in the caring sciences can be an enabler of better outcomes. Technological development and the adoption of new technology can also become a constraint and pose challenges to the current patterns of work and organizational elements. A framework for decision making of when to purchase and incorporate new technology is required.Purpose: This paper aimed to determine what is known of procurement decisions of advanced technology in healthcare generally and particularly in Indonesia.Methods: A scoping review was conducted to ascertain the current understanding of what forms the basis of procurement decisions of health technology generally and particularly in Indonesia. Â Â Results: A paucity of peer review literature was identified. There was no identified peer reviewed literature with a focus on Indonesia. Without a guiding evidence base and agreed decision making framework, it is likely that there is great variation in practices.Conclusion: In the absence of a solid body of literature to inform practices, two principals to move to a sustainable adoption and integration of advancing and emerging technology into practice in the health care sciences are presented, and provide a scaffold to facilitate navigating what can be tricky waters constituted by enthusiasm and trepidation.